Surface wear of attachments in patients during clear aligner therapy: a prospective clinical study - Qiuying Li; Kai Yang (Progress in Orthodontics, 2024)
Abstract Background This prospective clinical study aimed to quantitatively evaluate the surface wear of attachments and investigate the associated risk factors. Additionally, the wear values and regions of three types of commonly used attachments were explored. Methods Participants were recruited from the population of patients who received clear aligner therapy from October to December 2022. Intraoral scanning was performed on eligible participants before treatment (T0), immediately after initial bonding of attachments (T1), and at 2 months (T2), 4 months (T3), 6 months (T4), and 8 months (T5) after starting treatment. The attachment volume, average depth and regions of attachment wear were measured using superimposed digitized models. The Kruskal–Wallis test was performed to compare data between multiple groups. Multiple linear regression analyses were performed to evaluate risk factors for the volume of attachment wear. Results A total of 47 patients with 617 attachments were included. As treatment time increased, the attachment volume decreased significantly (P = 0.003). The initial attachment volume was positively related to the volume of attachment wear (β = 0.527, P < 0.001). The volume of attachment wear was significantly greater in females than in males (β = 0.147, P = 0.020) and in optimized attachments than in conventional attachments (β = 0.308, P < 0.001). The wear of 3-mm rectangular attachments progressed from edges to buccal surfaces, with the deepest wear at corners of gingival edges; the wear of the optimized attachments was primarily located on surface ridges. The wear volume ratio of the optimized root control attachments was significantly greater than that of the 3-mm rectangular attachments at T3 (P = 0.011), T4 (P < 0.001), and T5 (P < 0.001). Conclusions The volume of attachment wear increased gradually with treatment time. Sex, attachment type, and initial attachment volume were risk factors for the volume of attachment wear. The deepest wear regions of 3-mm rectangular attachments were at the corners of gingival edges, while the deepest wear regions of optimized attachments were at surface ridges. Four months after treatment, optimized root control attachments showed more relative wear than 3-mm rectangular attachments.